Setting the stage for international spent nuclear fuel storage facilities : international workshop proceedings - Schweitzer, Glenn E., 1930-; Robbins, Kelly (National Academies Press, 2008)
In May 2003, the Russian Academy of Sciences and the National Academies organized an international workshop in Moscow on the scientific issues relevant to the establishment and operation of an international spent nuclear fuel storage facility in Russia. Given the broad international interest in this topic, the academies organized a second international workshop on important issues that were not on the agenda or were not adequately discussed at the first workshop. These issues included international monitoring at the facility, transportation requirements, liability and insurance concerns, and status of Russian legislation and regulations that are important in locating and operating a facility. Relevant experience from Europe, the United States, and Asia was also considered in this 2005 workshop. This book contains the papers presented at the 2005 workshop sessions, as well as proceedings from the 2003 workshop. Together they provide an overview of the issues, and useful background for those organizations and individuals involved in further development of an international spent nuclear fuel storage facility in Russia.